1990
DOI: 10.1098/rstb.1990.0050
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β: multifunctional regulator of differentiation and development

Abstract: Transforming growth factors-beta (TGF-beta) are 25 kilodalton (kDa) homodimeric peptides with multifunctional actions controlling the growth, differentiation and function of a broad range of target cells of both epithelial and mesenchymal derivation. They are expressed early in embryogenesis and their tissue-specific and developmentally dependent expression is strongly suggestive of an essential role in particular morphogenetic and histogenetic events. Five distinct TGF-beta s have been characterized so far, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(59 citation statements)
references
References 31 publications
2
56
1
Order By: Relevance
“…PDGF (1-8 U/ml) and IGF-II (0.5-12 ng/ml) did not stimulate migration, nor did acidic FGF (2-12 ng/ml) with or without heparin ( 1-100 pg/ml). Next affects kinetic behavioral properties ofdiverse types ofcells (30,31). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PDGF (1-8 U/ml) and IGF-II (0.5-12 ng/ml) did not stimulate migration, nor did acidic FGF (2-12 ng/ml) with or without heparin ( 1-100 pg/ml). Next affects kinetic behavioral properties ofdiverse types ofcells (30,31). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As migration ofBSC-1 cells is easily inhibited by the RGDS peptide that competes with fibronectin for its receptor, it is possible that fibronectin-integrin binding may participate in migration both in the presence and absence ofADP, as appears to be the case in other types of cells. TGF-f has been shown to modulate cellular production of matrix proteins, plasminogen activator, and plasminogen activator inhibitor (30,47), and EGF stimulates transcription of integrins in 3T3 fibroblasts (48). In rat liver epithelial cells, EGF-induced migration is associated with altered fibronectin and laminin gene expression (49), and ECM proteins appear to modulate migration (50).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that genistein inhibits vessel endothelial cell proliferation and in vitro angiogenesis at half maximal concentration of 5 and 150 μM, respectively, suggesting that genistein is a potent inhibitor of vascularization and cancer cell growth [104]. TGF-β is a known major factor that regulates cell proliferation [115], and TGF-β signaling is an important feature in the up-regulation of angiogenesis [116]. Genistein has been known to inhibit TGF-β signaling, and therefore inhibit angiogenesis [116].…”
Section: Effects On the Inhibition Of Angiogenesis And Metastasismentioning
confidence: 99%
“…TGF-␤ regulates cell growth, cell differentiation, immune and inflammatory responses, extracellular matrix production, and apoptosis (22,23). TGF-␤ signaling is mediated by transmembrane serine/threonine kinase receptors that phosphorylate the receptor-regulated Smads, Smad2 and Smad3.…”
mentioning
confidence: 99%